Verification of Compliance by the Audited Entity with the Requirements of Laws and Regulations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is devoted to current issues of compliance by the audited entity with the requirements of laws and regulations related to the organization and the industry. The auditor should get an idea of the subject's compliance with these regulations. Particular attention should be paid to laws and regulations that may affect the organization's activities.This study explores the verification of compliance by audited entities with laws and regulations, emphasizing its critical role in financial auditing. Despite existing frameworks such as International Standard on Auditing (ISA) 250, gaps persist in identifying and addressing non-compliance, particularly in industries with complex regulatory requirements. This research adopts a qualitative approach, analyzing audit procedures, risk assessments, and internal controls to evaluate compliance mechanisms. The findings indicate that auditors face inherent limitations in detecting non-compliance due to regulatory complexity, management collusion, and inadequate internal controls. The results highlight the necessity of integrating advanced monitoring systems, improved legal consultations, and stronger regulatory enforcement to mitigate audit risks. The implications suggest that regulatory bodies and audit firms must enhance compliance verification methods, ensuring greater financial transparency and legal adherence. Strengthening audit frameworks will improve corporate governance, reduce financial misstatements, and foster investor confidence in regulatory compliance.